Electrical and dielectric analysis of phosphate based glasses doped with alkali oxides. (5th December 2015) - Graça, M.P.F.; Melo, B.M.G.; Prezas, P.R.; Valente, M.A.; Freire, F.N.A.; Bih, L.
Abstract: In this work, new phosphate glasses with the molar composition 20.7P2 O5 –17.2Nb2 O5 –13.8WO3 –34.5A2 O–13.8B2 O3 where A = Li, Na and K were prepared using the melt quenching technique. These types of glasses have potential to absorb hydrogen in its structure, which makes them promising materials to be used as electrolytes in intermediate temperature fuel cells. Additionally, niobium phosphate glasses can also have applications such as glass fibers, optical lenses, hermetic sealing and electrodes. The structure of the obtained samples was analyzed using Differential Thermal Analysis (DTA), X-ray powder diffraction (XRD), and Raman spectroscopy and the morphology by Scanning Electron Microscopy (SEM). The DTA measurements revealed values of glass transition temperature around 415 °C, and the Raman analysis showed that the amount of alkali and niobium oxides included on the studied compositions, successfully disrupted the P–O–P chains characteristic of the phosphate glasses. Dc (σdc ) and ac (σac ) conductivities and dielectric spectroscopy measurements were performed as function of the temperature (200–370 K) which presented conductivity predominantly ionic (σelectronic /σionic of about 10 − 4 ). The dielectric spectroscopy was measured in the frequency range 100–1 MHz. Graphical abstract: Highlights: 20.7P2 O5 –17.2Nb2 O5 –13.8WO3 –34.5A2 O–13.8B2 O3 (A = Li, Na, K) glasses were prepared. Promising glasses for hydrogen absorption/storage Relaxation kinetics with dielectric modulus formalism has an Arrhenius dependency. Dc conductivity at < 250 K is due to electron hopping between W 6 + –W 5 + and Nb 5 + –Nb 4 + . Promising glasses for electrolytes of intermediate temperature fuel cells